THEORETICAL ASPECTS OF FORMATION OF INNOVATIVE BUSINESS MARKETING STRATEGIES OF BUSINESS ENTITIES - HIL, Boris (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The acceleration of global digitalization of economic processes and increased competition in domestic and foreign markets are accelerating the decline of traditional approaches to promoting goods and services. These processes require the search for innovative business marketing strategies based on the integration of up-to-date digital tools and adaptive mechanisms of interaction with the market. Since innovative strategies involve the creation of new approaches to attracting and retaining customers based on current trends in the development of the digital environment, the study of the theoretical foundations of their formation is important both for the development of marketing science and for the practice of business management. Determining the theoretical aspects of innovative business marketing strategies is necessary for the development of effective promotion models that can ensure the sustainable development of business entities in the context of digital transformation and increased competition.The study analyzed scientific approaches to understanding the basic concepts of «innovation», «strategy», «business», «marketing», «innovation strategy», «business marketing», «entity» «economic activity» and «economic entity» which form the conceptual and categorical basis of the topic. The generalization of these approaches allowed the author to identify the structural elements of the process of forming innovative business marketing strategies and to substantiate the interdisciplinary nature of this category. The author’s definitions of key terms are formulated, in particular, «formation of innovative business marketing strategies of business entities», which is considered as a purposeful process of developing and implementing innovation-oriented marketing approaches within the framework of strategic management of an enterprise in the context of digital transformation.The functional load of the innovation strategy in strategic management is analyzed. The classification approaches to the interpretation of each of the basic categories are systematized, which made it possible to reveal the relationships between them and build a logical and semantic structure, presented in Figure 5, as a visual model of the categorical framework of the study.The study proves that innovative business marketing strategies are an important tool for strategic positioning of an enterprise, which allows not only to adapt to changes but also to form new market trends, ensuring competitive advantages and sustainable growth. The proposed theoretical generalization can serve as a basis for further empirical research and practical modeling of innovative strategies in the business marketing system.
Keywords: innovation; strategy; innovation strategy; business; marketing; business marketing; innovative business marketing strategies